Perancangan Situs Web Tour Organizer Setapak Teratour Dengan Pendekatan Human Centered Design - Juanshar Wicaksono Fajrin; Ismiarta Aknuranda; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Setapak Teratour is a business company engaged in field of travel organizer that want a website to help them advertise their tour package, provide an easier way for prospective buyers to make transaction, and give prospective buyers a better way to communicate with Setapak Teratour's staff. One of the method that can be used in desinging a website is Human Centered Design (HCD) method. This method is a designing method that focuses on human factors in the process. The stages of this research is follow the stages in Human Centered Design, namely (1) understand and specify the context of use which produces list of stakeholders and their characteristic; (2) specify the user requirements that obtained by doing interview with 5 (five) respondents; (3) produce design solution; (4) evaluate the design solution by doing interview with 5 (five) respondent and generate 9 improvement suggestion for user interface, and (5) improve the design by reffering to improvement suggestion from evaluation process. The final results of this research is an improved website user interface design from the previous one and refers to the evaluation result from the respondents.